Associations between ethylene oxide exposure and chronic bronchitis: results from the NHANES 2013–2018 - Yan Li; Hui Wang; Xiaoqing Bi; Guowei Zhao (Frontiers in Public Health)
IntroductionEthylene oxide (EtO) is a reactive gas commonly used in the production of various chemical compounds. Research has linked EtO exposure to respiratory conditions, including chronic obstructive pulmonary disease (COPD) and asthma. However, its potential effects on chronic bronchitis (CB) remain unclear, highlighting the need for further study to understand its role in respiratory health.MethodsOur study investigated data from 5,044 NHANES participants between 2013 and 2018 across three 2-year survey cycles. The relationship between HbEtO and CB was examined using weighted logistic regression, with HbEtO quartiles analyzed to assess the trend. A smoothed curve was fitted to verify the relationship between HbEtO and CB. Additionally, sensitivity analyses were conducted to assess the robustness of our results, while subgroup analyses explored potential effect modifiers of the HbEtO-CB association.ResultsCompared with patients without CB, patients with CB had elevated HbEtO levels. Specifically, natural Log2HbEtO levels were linked to a greater prevalence of CB in a fully adjusted model (OR = 1.243, 95% CI: 1.143–1.352). Analysis of Log2HbEtO quartiles showed a significant trend in Q4 compared with Q1 (p for trend < 0.001). The fitted smoothed curve indicated a U-shaped nonlinear association, with saturation and threshold analysis revealing an inflection point at Log2HbEtO = 4.87. Sensitivity analyses confirmed the robustness of these findings, and subgroup analyses identified consistent associations across various groups.ConclusionOur study found a significant association between EtO exposure and the occurrence of CB. Given the health risks linked to EtO exposure, implementing effective control measures is essential. Such actions could help lower CB prevalence and enhance respiratory health in vulnerable populations.